1992
DOI: 10.1172/jci115987
|View full text |Cite
|
Sign up to set email alerts
|

L-arginine improves endothelium-dependent vasodilation in hypercholesterolemic humans.

Abstract: Endothelium-dependent vasodilation is impaired in hypercholesterolemia, even before the development of atherosclerosis. The purpose of this study was to determine whether infusion of L-arginine, the precursor of the endothelium-derived relaxing factor, nitric oxide, improves endothelium-dependent vasodilation in hypercholesterolemic humans. Vascular reactivity was measured in the forearm resistance vessels of 11 normal subjects (serum LDL cholesterol = 2.76±0.10 mmol/liter) and 14 age-matched patients with hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
320
3
13

Year Published

1993
1993
2007
2007

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 731 publications
(347 citation statements)
references
References 49 publications
8
320
3
13
Order By: Relevance
“…Abnormal vascular control has not been reported previously in SCI patients. However, abnormal vascular control has been seen in a variety of conditions including: aging, 14,15 race, 16,17 hypercholesterolemia, 18,19 obesity, 20 diabetes 21 ± 24 and examples of muscle deconditioning after 14 ± 20 days of bed rest. 24 ± 27 Furthermore, untrained individuals have been shown to have poor orthostatic tolerance when compared to trained individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal vascular control has not been reported previously in SCI patients. However, abnormal vascular control has been seen in a variety of conditions including: aging, 14,15 race, 16,17 hypercholesterolemia, 18,19 obesity, 20 diabetes 21 ± 24 and examples of muscle deconditioning after 14 ± 20 days of bed rest. 24 ± 27 Furthermore, untrained individuals have been shown to have poor orthostatic tolerance when compared to trained individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups demonstrated that acute and chronic supplementation of L-arginine improves endothelial vasodilator responses in cholesterol fed animals and in patients with hypercholesterolemia and atherosclerosis [20][21][22][23]. Following these early studies, numerous studies with supplemental Larginine therapy have been conducted in animal models and in humans; however, no consistent results can be achieved [24••].…”
Section: Controversy Of L-arginine Supplemental Therapy In Atherosclementioning
confidence: 99%
“…It has been well documented that endothelium-dependent vasodilation is impaired in both animal models of atherosclerosis (Freiman et al, 1986;Kolodgie et al, 1990) and in atherosclerotic human coronary arteries (Bossaler et al, 1987;FoÈ rstermann et al, 1988;Zeiher et al, 1991). In addition, risk factors for the development of atherosclerosis such as hypercholesterolemia are associated with impaired endothelial function (Creager et al, 1992).…”
Section: Introductionmentioning
confidence: 99%